(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the educational, moral, and social significance of national values and traditions in the formation of a harmonious generation. A harmonious generation is understood as a cohort of young people whose intellectual development, ethical responsibility, civic consciousness, emotional stability, and cultural identity evolve in balance rather than in isolation. The study argues that national values and traditions should not be reduced to symbolic heritage or ceremonial repetition. Their deeper pedagogical function lies in transmitting norms of conduct, collective memory, intergenerational continuity, social solidarity, and respect for human dignity. At the same time, the article maintains that traditions become educationally productive only when they are interpreted critically and aligned with universal principles such as equality, tolerance, and the rights of the child.